Chloroquine is grossly under dosed in young children with malaria: implications for drug resistance. - Johan Ursing; Staffan Eksborg; Lars Rombo; Yngve Bergqvist; Daniel Blessborn; Amabelia Rodrigues; Poul-Erik Kofoed (PLoS ONE, 2014)
Plasmodium falciparum malaria is treated with 25 mg/kg of chloroquine (CQ) irrespective of age. Theoretically, CQ should be dosed according to body surface area (BSA). The effect of dosing CQ according to BSA has not been determined but doubling the dose per kg doubled the efficacy of CQ in children aged <15 years infected with P. falciparum carrying CQ resistance causing genes typical for Africa. The study aim was to determine the effect of age on CQ concentrations.Day 7 whole blood CQ concentrations were determined in 150 and 302 children treated with 25 and 50 mg/kg, respectively, in previously conducted clinical trials. CQ concentrations normalised for the dose taken in mg/kg of CQ decreased with decreasing age (p<0.001). CQ concentrations normalised for dose taken in mg/m(2) were unaffected by age. The median CQ concentration in children aged <2 years taking 50 mg/kg and in children aged 10-14 years taking 25 mg/kg were 825 (95% confidence interval [CI] 662-988) and 758 (95% CI 640-876) nmol/l, respectively (p = 0.67). The median CQ concentration in children aged 10-14 taking 50 mg/kg and children aged 0-2 taking 25 mg/kg were 1521 and 549 nmol/l. Adverse events were not age/concentration dependent.CQ is under-dosed in children and should ideally be dosed according to BSA. Children aged <2 years need approximately double the dose per kg to attain CQ concentrations found in children aged 10-14 years. Clinical trials assessing the efficacy of CQ in Africa are typically performed in children aged <5 years. Thus the efficacy of CQ is typically assessed in children in whom CQ is under dosed. Approximately 3 fold higher drug concentrations can probably be safely given to the youngest children. As CQ resistance is concentration dependent an alternative dosing of CQ may overcome resistance in Africa.